Goethe und die Juden - die Juden und Goethe Beiträge zu einer Beziehungs- und Rezeptionsgeschichte - Ludewig, Anna-Dorothea; Höhne, Steffen (Europäisch-jüdische Studien - Beiträge, 2018)
Starting out from Goethe`s ambivalent relationship to Jews and Judaism, this volume addresses the varied reception of Goethe`s person and works in the context of German-Jewish cultural history. For the first time, Goethe`s personal relationship to Jewish contemporaries and their relationship to him are correlated with the reception of his work by Jewish scholars and readers. The anti-Semitic appropriation of Goethe is additionally discussed.